Particulate matter in the indoor environment of museums in the megacity of São Paulo - Andrea Cavicchioli; Ericka Pardini Morrone; Adalgiza Fornaro (Química Nova, 2014)
Atmospheric pollutants can have serious impacts on the preservation of São Paulo's tangible cultural heritage. The purpose of this paper is to report the results of a monitoring campaign focussed on particulate matter (PM) that was conducted in three of the most important museums of the São Paulo megacity (Brazil): the Museu de Arqueologia e Etnologia (MAE-USP), the Museu Paulista (MP-USP), and the Pinacoteca do Estado de São Paulo (PE). These museums exhibit indoor PM and black carbon (BC) concentrations consistent with their urban locations and their specific methods for managing the indoor environment.